Lithium nickel-based composite oxides as positive electrode active materials for rechargeable solid-state batteries
The formulation of a positive electrode active substance with controlled Li, Ni, Mn, Co, and ZR ratios in a lithium transition metal oxide compound mixture enhances battery efficiency by optimizing carbon content and processing methods, addressing the low efficiency of existing materials.
Patent Information
- Application Number
- JP2024535982
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-17
- Filing Date
- 2022-12-16
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-12-16
AI Technical Summary
Existing lithium nickel oxide positive active materials for solid batteries exhibit low efficiency when used in solid batteries, necessitating an improvement in their performance.
A positive electrode active substance is formulated with specific compositions of Li, M', and O, where M' includes Ni, Mn, Co, and optionally other elements, with controlled ratios of these components and a ZR content, prepared by mixing lithium transition metal oxide compounds in an alcohol and water slurry, followed by filtration and heating, to enhance efficiency.
The improved formulation results in higher efficiency of solid batteries, with enhanced electrochemical performance and increased carbon content optimization, leading to improved battery efficiency.
Smart Images

Figure 2025502672000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a cathode active material for solid-state rechargeable batteries. More specifically, the present invention relates to a cathode active material comprising Zr for solid-state batteries, preferably the solid-state battery is a sulfide-based all-solid-state battery. The present invention also relates to a method for producing the cathode active material. Furthermore, the present invention relates to a solid-state battery comprising the cathode active material, and to the use of the cathode active material in a solid-state battery. [Background technology]
[0002] Lithium nickel-based oxide positive electrode active materials containing Zr compounds applicable to solid-state batteries are already known, for example, from the literature ACS Appl. Mater. Interfaces 2020, 12, 51, 57146-57154. This literature discloses a positive electrode active material containing Li, M', and O mixed with Zr ethoxide in an ethanol solvent, where M' is Ni 0.6 Co 0.2 Mn 0.2 The treatment with Zr ethoxide produces a cathode active material with low efficiency when applied to solid-state batteries. Therefore, there is a need to provide a lithium nickel-based oxide cathode active material containing a Zr compound with improved efficiency in solid-state batteries.
[0003] An object of the present invention is to provide a positive electrode active material containing Zr.
[0004] A further object of the present invention is to provide a method for producing the positive electrode active material.
[0005] It is a further object of the present invention to provide a solid-state battery including the positive electrode active material.
[0006] A further object of the present invention is to provide a use of the cathode active material in a solid-state battery. Summary of the Invention
[0007] The object is to provide a cathode active material for a solid-state battery, the cathode active material comprising Li, M' and oxygen, wherein M' is Ni with a content x, where x is 55.0 mol% or less and 95.0 mol% or less with respect to M'; Mn with a content y of 0.0mol%≦y≦40.0mol%; Co with a content z of 0.0 mol% ≦ z ≦ 40.0 mol%; D with a content a of 0.0 mol%≦a≦2.0 mol%, where D is at least one element other than Li, Ni, Mn, Co, and O; Zr having a content b, where 0.01 mol%≦b≦5.0 mol%, x, y, z, a, and b are measured by ICP-OES; x+y+z+a+b is 100.0 mol%, The positive electrode active material has a Zr content of Zr x and Zr x was determined by XPS analysis, and Zr x is expressed as a mole fraction compared to the sum of the mole fractions of Co, Mn, Ni, and Zr as determined by XPS analysis, the positive electrode active material comprises carbon in a content C as measured by a carbon analyzer, C being in weight percent; Zr x This is achieved by providing a positive electrode active material having a ratio of Zn-C between 52-0.413·x and 42-0.413·x.
[0008] The inventors have surprisingly found that by mixing a slurry of a lithium transition metal based oxide compound, a source of Zr in alcohol, and water, followed by filtering the mixture, the resulting cathode active material has a lower ratio of Zr content to carbon content as compared to an cathode active material conventionally produced by preparing a mixture of a lithium transition metal based oxide compound and a Zr alkoxide in ethanol, followed by evaporating the ethanol from the mixture, as demonstrated in the accompanying examples. [Brief description of the drawings]
[0009] [Figure 1] The graph shows the Ni / M' content (x) of the positive active material in atomic % (x-axis) versus Zr / C (ratio of Zr / (Ni+Mn+Co+Zr) to carbon content (wt %) as measured by XPS; y-axis). The patterned areas represent the areas claimed in this invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] In order to enable the practice of the invention, preferred embodiments are described in detail in the drawings and the following detailed description. Although the invention has been described with reference to these specific preferred embodiments, it will be understood that the invention is not limited to these preferred embodiments. On the contrary, the invention includes numerous alternatives, modifications and equivalents, as will become apparent from a consideration of the following detailed description and the accompanying drawings.
[0011] The term "comprising" as used in the present specification and claims should not be interpreted as being limited to the means recited thereafter, and does not exclude other elements or steps. It should be interpreted as specifying the presence of the mentioned features, integers, steps, or components as mentioned, but does not exclude the presence or addition of one or more other features, integers, steps, or components, or groups thereof. Thus, the scope of the expression "a composition comprising components A and B" should not be limited to a composition consisting of components A and B only. It means that in the context of the present invention, the only relevant components of the composition are A and B. Thus, the terms "comprising" and "including" encompass the more restrictive terms "consisting essentially of" and "consisting of".
[0012] The positive electrode active material is defined as a material that is electrochemically active in the positive electrode, which is understood to be a material that can capture and release Li-ions when exposed to a voltage change for a given period of time.
[0013] positive electrode active material In a first aspect, the present invention provides a cathode active material for a solid-state battery, the cathode active material comprising Li, M′, and oxygen, wherein M′ is Ni with a content x of 55.0 mol%≦x≦95.0 mol%; Mn with a content y of 0.0mol%≦y≦40.0mol%; Co with a content z of 0.0 mol% ≦ z ≦ 40.0 mol%; D with a content a of 0.0 mol%≦a≦2.0 mol%, where D is at least one element other than Li, Ni, Mn, Co, and O; Zr having a content b, where 0.01 mol%≦b≦5.0 mol%, x, y, z, a, and b are measured by ICP-OES; x+y+z+a+b is 100.0 mol%, The positive electrode active material has a Zr content of Zr x and Zr x was determined by XPS analysis, and Zr x is expressed as a mole fraction compared to the sum of the mole fractions of Co, Mn, Ni, and Zr as determined by XPS analysis, the positive electrode active material comprises carbon in a content C as measured by a carbon analyzer, C being in weight percent based on the total weight of the positive electrode active material; Zr x and C is 52-0.413·x to 42-0.413·x.
[0014] Zr, 52-0.413 x ~ 42-0.413 x x The ratio of C to β is shown in Figure 1.
[0015] Preferably, Zr xThe ratio of Zr to C is 50 - 0.413·x to 43 - 0.413·x.
[0016] As would be understood by those skilled in the art, the x unit of the ratio of Zr to C is (wt%). -1 It is.
[0017] In a preferred embodiment, Ni has a content of x ≥ 60.0 mol%, preferably x ≥ 61.0 mol%, more preferably x ≥ 62.0 mol%. In a preferred embodiment, x ≤ 90.0 mol%, preferably x ≤ 88 mol%, more preferably x ≤ 85.0 mol%.
[0018] A more preferred embodiment is the positive electrode active material of the present invention, wherein the content x of Ni is 55.0 mol% ≤ x ≤ 75.0 mol%, preferably 60.0 mol% ≤ x ≤ 70.0 mol%, more preferably 62.0 mol% ≤ x ≤ 68.0 mol%.
[0019] A more preferred embodiment is the positive electrode active material of the present invention, wherein the content x of Ni is 75.0 mol% < x ≤ 95.0 mol%, preferably 76.0 mol% ≤ x ≤ 90.0 mol%, more preferably 77.0 mol% ≤ x ≤ 88.0 mol%.
[0020] As would be understood by those skilled in the art, the amounts of Li and M' in the positive electrode active material, preferably Li, Ni, Mn, Co, D, and Zr, are measured by Inductively Coupled Plasma - Optical Emission Spectroscopy (ICP - OES). For example, without limiting the present invention, Agilent ICP 720 - ES is used in ICP - OES analysis.
[0021] In a preferred embodiment, Mn has a content of y > 0.0 mol%, more preferably y ≥ 5.0 mol%, and even more preferably y ≥ 8.0 mol%. In a preferred embodiment, the content is y ≤ 40.0 mol%, preferably y ≤ 30.0 mol%, and more preferably y ≤ 25.0 mol%. In a preferred embodiment, the content is 0.0 mol% < y ≤ 40.0 mol%, preferably 5.0 mol% ≤ y ≤ 8.0 mol%, and more preferably 8.0 mol% ≤ y ≤ 25.0 mol%.
[0022] In a preferred embodiment, Co has a content of z > 0.0 mol%, more preferably z ≥ 1.0 mol%, and even more preferably z ≥ 3.0 mol%. In a preferred embodiment, the content is z ≤ 40.0 mol%, more preferably z ≤ 30.0 mol%, and even more preferably z ≤ 25.0 mol%. In a preferred embodiment, the content is 0.0 mol% < z ≤ 40.0 mol%, preferably 1.0 mol% ≤ z ≤ 30.0 mol%, and more preferably 3.0 mol% ≤ z ≤ 25.0 mol%.
[0023] In a preferred embodiment, D is at least one element other than Li, Ni, Mn, Co, Zr, and O.
[0024] In a preferred embodiment, D includes at least one element from the group consisting of Al, B, Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, Ti, Y, V, W, and Zn, preferably at least one element from the group consisting of Al, B, Cr, Nb, S, Si, Ti, Y, and W.
[0025] In a very preferred embodiment, D is at least one element from the group consisting of Al, B, Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, Ti, Y, V, W, and Zn, preferably Al, B, Cr, Nb, S, Si, Ti, Y, and W, and more preferably at least one element from the group consisting of Al, B, Nb, Ti, and W.
[0026] In a preferred embodiment, D has a content of a > 0.0 mol%, more preferably a ≥ 0.25 mol%, and even more preferably a ≥ 0.5 mol%. In a preferred embodiment, the content is a ≤ 2.0 mol%, preferably a ≤ 1.75 mol%, and more preferably a ≤ 1.5 mol%. In a preferred embodiment, the content is 0.0 mol% < a ≤ 2.0 mol%, preferably 0.25 mol% ≤ a ≤ 1.75 mol%, and more preferably 0.5 mol% ≤ a ≤ 1.5 mol%.
[0027] A preferred embodiment is the positive active material of the present invention, wherein Zr has a content of b > 0.01 mol%, preferably b ≥ 0.05 mol%, and more preferably b ≥ 0.10 mol%. In a preferred embodiment, b ≤ 2.5 mol%, preferably b ≤ 2.0 mol%, and more preferably b ≤ 2 mol%. In a preferred embodiment, 0.05 mol% ≤ b ≤ 2.5 mol%, preferably 0.10 mol% ≤ b ≤ 2.0 mol%, and more preferably 0.15 mol% ≤ b ≤ 2.0 mol%.
[0028] A specific preferred embodiment is the positive active material of the present invention, wherein Zr has a content of b > 0.01 mol%, preferably b ≥ 0.05 mol%, and more preferably b ≥ 0.10 mol%. In a preferred embodiment, b ≤ 2.5 mol%, preferably b ≤ 2.0 mol%, and more preferably b ≤ 1.5 mol%. In a preferred embodiment, 0.05 mol% ≤ b ≤ 2.5 mol%, preferably 0.10 mol% ≤ b ≤ 2.0 mol%, and more preferably 0.15 mol% ≤ b ≤ 1.5 mol%.
[0029] In particular, Zr xis the mole fraction of Zr measured in a region of a secondary particle or single crystal particle of the positive electrode active material according to the present invention, defined between a first point on the outer edge of the particle and a second point at a certain distance from the first point. The distance separating the first point and the second point is equal to the XPS penetration depth, and the penetration depth D is 1.0 to 10.0 nm. In particular, the penetration depth is the distance along an axis perpendicular to a virtual line tangent to the outer edge and passing through the first point.
[0030] The outer edge of a particle is, within the framework of the present invention, the boundary or outer limit which distinguishes the particle from its external environment.
[0031] Thus, the XPS analysis provides the atomic content of the element in the top layer of the particle with a penetration depth of about 10.0 nm from the outer boundary of the particle. The outer boundary of the particle is also called the "surface". In the framework of the present invention, atomic % means atomic percentage. Atomic % or "atomic percent" as a concentration expression of a given element means what percentage of all atoms in the relevant compound are atoms of that element. The term atomic % is equivalent to mol % or "mole percent". For example, and without limiting the present invention, the XPS analysis is performed using a Thermo K-α+ spectrometer (Thermo Scientific).
[0032] A preferred embodiment has a ratio of Zr x / b>100, preferably Zr x / b>150, more preferably Zr x / b>200. A preferred embodiment is a positive electrode active material having a ratio of Zr x / b<1000, preferably Zr x / b<500, more preferably Zr x A preferred embodiment of the positive electrode active material of the present invention has a ratio Zrx / b of 100 or less. <Zr x / b<1000, preferably 150 <Zr x / b<500, preferably 200 <Zr x / b<350.
[0033] As will be appreciated by those skilled in the art, the defined ratio Zr x / b indicates that the positive electrode active material of the present invention has an enriched amount of Zr in the surface layer of the positive electrode active material. The surface layer of the positive electrode active material is the top 1-10 nm of the positive electrode active material. In other words, the positive electrode active material of the present invention includes a coating layer of Zr. In the context of the present invention, the positive electrode active material may include a further coating layer containing D, where D is at least one element of the group consisting of Al, B, Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, Ti, Y, V, W, and Zn, preferably Al, B, Cr, Nb, S, Si, Ti, Y, and W, and the coating layer of Zr may be disposed on the further coating layer, and / or the further coating layer may be disposed on the coating layer of Zr, and / or the positive electrode active layer may include a mixed coating layer including a coating layer of Zr and a further coating layer.
[0034] A preferred embodiment is a cathode active material of the present invention, in which C≦0.15 wt%, preferably C≦0.12 wt%, more preferably C≦0.11 wt%, based on the total weight of the cathode active material. A preferred embodiment is a cathode active material of the present invention, in which C≧0.01 wt%, preferably C≧0.02 wt%, more preferably C≧0.03 wt%, based on the total weight of the cathode active material. A preferred embodiment is a cathode active material of the present invention, in which C is in an amount of 0.01 wt% to 0.15 wt%, preferably 0.02 wt% to 0.12 wt%, more preferably 0.03 wt% to 0.11 wt%, based on the total weight of the cathode active material. As will be appreciated by those skilled in the art, the carbon content of the cathode active material of the present invention is measured with a carbon analyzer. For example, but not by way of limitation to the present invention, the carbon content C can be measured using a Horiba Emia-Expert carbon / sulfur analyzer.
[0035] In a preferred embodiment, the positive electrode active material is 0.15 m 2 / g, preferably 0.25m 2 / g, more preferably 0.45m 2 / g.
[0036] In a preferred embodiment, the positive electrode active material is 2 / g, preferably less than 0.90m 2 / g, more preferably less than 85m 2 In a preferred embodiment, the positive electrode active material has a surface area SA of less than 0.15 m 2 / g~1m 2 / g, preferably 0.25m 2 / g~0.90m 2 / g, more preferably 0.45m 2 / g~0.85m 2 The surface area SA is determined by BET measurements, as will be understood by those skilled in the art. For example, and not limiting of the present invention, the surface area can be determined using a Micromeritics Tristar II 3020.
[0037] In a preferred embodiment, the cathode active material of the present invention has a secondary particle median diameter D50 of at least 1.0 μm, preferably at least 2.0 μm, and more preferably at least 3.0 μm. In a preferred embodiment, the cathode active material of the present invention has a secondary particle median diameter D50 of at most 20.0 μm, preferably at most 15.0 μm, and more preferably at most 10.0 μm. In a preferred embodiment, the cathode active material of the present invention has a secondary particle median diameter D50 in an amount of 1.0 μm to 20.0 μm, preferably in an amount of 2.0 μm to 15.0 μm, and more preferably in an amount of 3.0 μm to 10.0 μm. As will be appreciated by those skilled in the art, the secondary particle median diameter D50 is determined by laser diffraction particle size analysis. For example, but not by way of limitation to the present invention, the secondary particle median diameter D50 can be determined using a Malvern Mastersizer 3000.
[0038] In a preferred embodiment, the positive electrode active material is a single crystal powder, or in a more preferred embodiment, the positive electrode active material is a polycrystalline powder.
[0039] The concept of single crystal powder is well known in the art of cathode active materials. It relates to powders having predominantly single crystal particles. Such powders are a separate type of powder compared to polycrystalline powders made from particles that are predominantly polycrystalline. Those skilled in the art can easily distinguish between these two types of powders based on microscopic images.
[0040] Single crystal particles are also known in the art as monolithic particles, integral particles or / and monocrystalline particles.
[0041] A technical definition of a single crystal powder is not necessary since such powders can be readily recognized by one skilled in the art using an SEM, however, in the context of the present invention, a single crystal powder may be considered to be defined as a powder in which 80% or more of the particles by number are single crystal particles. This means a powder having a size of at least 45 μm by at least 60 μm (i.e., at least 2700 μm 2 ), preferably at least 100 μm×100 μm (i.e., at least 10,000 μm 2 ) on an SEM image with a field of view.
[0042] A single crystal particle is a particle that is an individual crystal or is formed from less than five, preferably a maximum of three, primary particles that are themselves individual crystals. This can be observed by observing the grain boundaries with a suitable microscopic technique, such as a Scanning Electron Microscope (SEM). Thus, as will be appreciated by those skilled in the art, the determination of the secondary particle median size D50 is also applicable to single crystal powders.
[0043] In determining whether a particle is a single crystal particle, grains having a maximum linear dimension observed by SEM that is smaller than 20% of the median diameter D50 of the powder as determined by laser diffraction are ignored. This avoids inadvertently considering particles that are essentially single crystal but have some very small other grains, e.g., polycrystalline coatings deposited on them, as not being single crystal particles.
[0044] As will be appreciated by those skilled in the art, polycrystalline powders consist of secondary particles that include a plurality of primary particles, preferably greater than 20 primary particles, preferably greater than 10 primary particles, and most preferably greater than 5 primary particles.
[0045] As will be appreciated by those skilled in the art, the secondary particles that make up the polycrystalline powders defined herein are polycrystalline particles, and all embodiments relating to secondary particles apply equally to polycrystalline particles as defined herein.
[0046] In a highly preferred embodiment, the cathode active material of the material of the invention is a single crystal powder having a C to SA ratio greater than 0.01, preferably greater than 0.03, more preferably greater than 0.06. In a highly preferred embodiment, the cathode active material of the material of the invention is a single crystal powder having a C to SA ratio less than 0.20, preferably less than 0.15, more preferably less than 0.12. In a highly preferred embodiment, the cathode active material of the material of the invention is a single crystal powder having a C to SA ratio in the amount of 0.01 to 0.20, preferably in the amount of 0.03 to 0.15, more preferably in the amount of 0.06 to 0.12.
[0047] Certain highly preferred cathode active materials of the present invention are single crystal powders having a primary particle median D50 value of less than 10.0 μm, preferably less than 8.0 μm, more preferably less than 7.0 μm. In certain preferred embodiments, the cathode active materials of the present invention are single crystal powders having a primary particle median D50 value of greater than 1.0 μm, preferably greater than 2.0 μm, more preferably greater than 3.0 μm. In certain preferred embodiments, the cathode active materials of the present invention are single crystal powders having a primary particle median D50 value of 1.0 μm to 10.0 μm, preferably 2.0 μm to 8.0 μm, more preferably 3.0 μm to 5.0 μm. As will be appreciated by those skilled in the art, the particle size distribution (PSD) D50 of the cathode active material powder is measured by laser diffraction particle size analysis. For example, and not by way of limitation, the particle median D50 can be measured using a Malvern Mastersizer 3000.
[0048] In a highly preferred embodiment, the cathode active material of the material of the invention is a polycrystalline powder having a C to SA ratio greater than 0.10, preferably greater than 0.12, more preferably greater than 0.15. In a highly preferred embodiment, the cathode active material of the material of the invention is a polycrystalline powder having a C to SA ratio less than 0.25, preferably less than 0.22, more preferably less than 0.20. In a highly preferred embodiment, the cathode active material of the material of the invention is a polycrystalline powder having a C to SA ratio in the amount of 0.10 to 0.25, preferably in the amount of 0.12 to 0.22, more preferably in the amount of 0.15 to 0.20.
[0049] Certain highly preferred cathode active materials of the present invention are polycrystalline powders having a secondary particle median diameter D50 of at least 1.0 μm, preferably at least 2.0 μm, and more preferably at least 3.0 μm. In certain highly preferred embodiments, the cathode active materials of the present invention are polycrystalline powders having a secondary particle median diameter D50 of at most 20.0 μm, preferably at most 15.0 μm, and more preferably at most 10.0 μm. In preferred embodiments, the cathode active materials of the present invention are polycrystalline powders having a secondary particle median diameter D50 in an amount of 1.0 μm to 20.0 μm, preferably in an amount of 2.0 μm to 15.0 μm, and more preferably in an amount of 3.0 μm to 10.0 μm. As will be appreciated by those skilled in the art, the secondary particle median diameter D50 is determined by laser diffraction particle size analysis. For example, and not by way of limitation to the present invention, the secondary particle median diameter D50 can be determined using a Malvern Mastersizer 3000.
[0050] As will be appreciated by those skilled in the art, the ratio of C to SA is expressed in units of weight percent (g / m 2 ).
[0051] In a second aspect, the present invention provides a cathode active material for a solid-state battery, the cathode active material comprising Li, M′, and oxygen, wherein M′ is Ni with a content x of 55.0 mol% ≦ x ≦ 75.0 mol%, preferably 60.0 mol% ≦ x ≦ 70.0 mol%, more preferably 62.0 mol% ≦ x ≦ 68.0 mol%, Mn with a content y of 0.0mol%≦y≦40.0mol%; Co with a content z of 0.0 mol% ≦ z ≦ 40.0 mol%; D with a content a of 0.0 mol%≦a≦2.0 mol%, where D is at least one element other than Li, Ni, Mn, Co, and O; Zr having a content b, where 0.01 mol%≦b≦5.0 mol%, x, y, z, a, and b are measured by ICP-OES; x+y+z+a+b is 100.0 mol%, The positive electrode active material has a Zr content of Zr x and Zr x is determined by XPS analysis, and Zr x is expressed as a molar fraction compared to the total molar fractions of Co, Mn, Ni, and Zr determined by XPS analysis, The positive electrode active material contains carbon with a content C measured by a carbon analyzer, and C is in units of weight%, Zr x The ratio of Zr -1 to C is 10 to 30 (weight%), -1 preferably 15 to 25 (weight%), -1 more preferably 18 to 22 (weight%),
[0052] A very preferred embodiment is the positive electrode active material of the present invention, wherein D is at least one element other than Li, Ni, Mn, Co, Zr, and O.
[0053] As will be understood by those skilled in the art, all embodiments relating to the positive electrode active material according to the first aspect are applied by making the necessary changes to the positive electrode active material according to the second aspect.
[0054] In a third aspect, the present invention provides a positive electrode active material for a solid battery, wherein the positive electrode active material contains Li, M' and oxygen, and M' is Ni with a content x of 75.0 mol% < x ≦ 95.0 mol%, preferably 76.0 mol% ≦ x ≦ 90.0 mol%, more preferably 77.0 mol% ≦ x ≦ 88.0 mol%, Mn with a content y of 0.0 mol% ≦ y ≦ 40.0 mol%, Co with a content z of 0.0 mol% ≦ z ≦ 40.0 mol%, D with a content a of 0.0 mol% ≦ a ≦ 2.0 mol%, where D is at least one element other than Li, Ni, Mn, Co, and O, and Zr with a content b of 0.01 mol% ≦ b ≦ 5.0 mol%, where x, y, z, a, and b are measured by ICP - OES, x+y+z+a+b is 100.0 mol%, The positive electrode active material has a Zr content of Zr x and Zr x was determined by XPS analysis, and Zr x is expressed as a mole fraction relative to the sum of the mole fractions of Co, Mn, Ni, and Zr as determined by XPS analysis, the positive electrode active material comprises carbon with a content C as measured by a carbon analyzer, where C is in weight percent; Zr x The ratio of C to Zn is 7 to 30 (wt%). -1 , preferably 8 to 25 (wt%) -1 , more preferably 9 to 20 (wt%) -1 The present invention relates to a positive electrode active material,
[0055] A highly preferred embodiment is a cathode active material of the invention, where D is at least one element other than Li, Ni, Mn, Co, Zr, and O.
[0056] As will be appreciated by those skilled in the art, all embodiments relating to the cathode active material according to the first aspect apply mutatis mutandis to the cathode active material according to the third aspect.
[0057] Manufacturing method In a fourth aspect, the present invention also provides a method for producing a positive electrode active material, comprising: Preparing a slurry of a lithium transition metal based oxide compound, Li, water, and alcohol; mixing the slurry with a Zr source to obtain a mixture; and heating the mixture at a temperature between 250° C. and 500° C. in an oxidizing atmosphere for a time period between 1 hour and 20 hours.
[0058] A highly preferred embodiment is a method for making an active cathode material, wherein the active cathode material is according to the first aspect of the invention, according to the second aspect of the invention, and / or according to the third aspect of the invention.
[0059] In a preferred embodiment of the method, the lithium transition metal based oxide compound comprises Li, M' and oxygen, where M' comprises Ni, Mn, Co and D, where D is at least one element from the group consisting of Al, B, Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, Ti, Y, V, W and Zn; preferably, Al, B, Cr, Nb, S, Si, Ti, Y, W.
[0060] Preferably, the lithium transition metal oxide powders used are also typically prepared according to a lithiation process, i.e. a process in which a mixture of a transition metal precursor and a lithium source is heated, preferably at a temperature of at least 500° C. Typically, the transition metal precursor is prepared by co-precipitation of one or more transition metal sources, such as salts, preferably sulfates, of the M′ elements Ni, Mn and / or Co, in the presence of an alkali compound, such as an alkali hydroxide, for example sodium hydroxide and / or ammonia.
[0061] Preferably, the method comprises the further step of filtering and drying the mixture prior to heating the mixture. Preferably, the drying is carried out under vacuum or with N 2 This is carried out under a constant flow of gas for at least 4 hours and up to 20 hours.
[0062] In a preferred embodiment of the method, the Zr source is a Zr alkoxide, preferably Zr ethoxide, Zr propoxide or Zr butoxide, more preferably Zr propoxide. In a preferred embodiment, the Zr alkoxide is mixed with the mixture as a solid. Alternatively, more preferably, the Zr alkoxide is mixed with the slurry as a solution, the solution comprising Zr alkoxide and a further alcohol, the alkoxide group being the conjugate base of the further alcohol. For example, the Zr alkoxide is Zr propoxide dissolved in propanol. Typically, the solution comprises 50-90 wt% Zr alkoxide of the total weight of the solution. Examples of such solutions are 70 wt% Zr propoxide in 1-propanol, or 80 wt% Zr butoxide in 1-butanol.
[0063] Preferably, the alcohol solvent is methanol, ethanol, propanol or butanol, preferably ethanol.
[0064] In a preferred embodiment, the amount of water in the slurry is 0.5 mol% to 25.0 mol% based on the metal content in the lithium transition metal oxide compound, preferably 0.7 mol% to 10.0 mol%, more preferably 1 mol% to 5 mol% based on the metal content in the lithium transition metal oxide compound. In a preferred embodiment, the molar ratio of water to Zr alkoxide in the slurry is at least 2:1, preferably at least 3:1, more preferably at least 4:1. In a preferred embodiment, the molar ratio of water to Zr alkoxide in the slurry is at most 10:1, preferably at most 8:1, more preferably at most 6:1. In a preferred embodiment, the molar ratio of water to Zr alkoxide in the slurry is 2:1 to 10:1, preferably 3:1 to 8:1, more preferably 4:1 to 6:1.
[0065] A preferred embodiment of the method is to heat the mixture at a temperature between 275°C and 450°C, preferably between 300°C and 400°C, more preferably between 325°C and 375°C.
[0066] A preferred embodiment of the method is to heat the mixture, and the oxidizing atmosphere comprises or consists of oxygen, such as air.
[0067] Product by Process In a fifth aspect, the present invention relates to a cathode active material obtainable by the method according to the fourth aspect of the present invention.
[0068] As will be appreciated by those skilled in the art, all embodiments relating to the positive electrode active material according to the first aspect of the invention, the second aspect of the invention, the third aspect of the invention, and / or the method according to the fourth aspect of the invention apply mutatis mutandis to the positive electrode active material obtainable by the method according to the invention. For example, the Li, M', Zr content Zrx The various embodiments regarding the identity and amount of the carbon content C are equally applicable to the positive electrode active material obtainable by the method for preparing the positive electrode active material.
[0069] battery In a sixth aspect, the present invention relates to a battery comprising an active cathode material according to the first aspect of the invention, the second aspect of the invention, and / or the third aspect of the invention.
[0070] In a preferred embodiment, the battery is a solid-state battery. Preferably, the solid-state battery comprises a sulfide-based electrolyte. Preferably, the electrolyte is a sulfide-based solid electrolyte, more preferably, the electrolyte comprises Li, P, and S. In a highly preferred embodiment, the battery is a sulfide solid-state battery.
[0071] In a preferred embodiment, the battery according to the invention has an efficiency of at least 88%, preferably at least 90%, more preferably at least 92%, and most preferably at least 94%. As will be appreciated by those skilled in the art, the efficiency of a battery is determined as described under section D) of the Examples.
[0072] use In a seventh aspect, the present invention relates to the use of an active cathode material according to the first aspect of the invention, the second aspect of the invention, and / or the third aspect of the invention in a battery.
[0073] A preferred embodiment is the use of the positive electrode active material in a battery, preferably a solid-state battery, more preferably a sulfide solid-state battery, to increase the efficiency of the battery.
[0074] In an eighth aspect, the present invention relates to the use of a battery according to the present invention in any one of a portable computer, a tablet, a mobile phone, an energy storage system, an electric vehicle or a hybrid electric vehicle, preferably in an electric vehicle or a hybrid electric vehicle. EXAMPLES
[0075] A) ICP analysis The amount of Li, Ni, Mn, Co, and Zr in the positive electrode active material powder is measured by inductively coupled plasma (ICP-OES) method by using Agilent ICP 720-ES. 2 grams of powder sample is dissolved in 10 mL of high purity hydrochloric acid (at least 37 wt% HCl with respect to the total weight of the solution) in an Erlenmeyer flask. The flask is covered with glass and heated on a hot plate at 380 °C until the powder is completely dissolved. After cooling to room temperature, the solution in the Erlenmeyer flask is poured into a 250 mL volumetric flask. The volumetric flask is then filled with deionized water up to the 250 mL mark, and then homogenized thoroughly. An appropriate amount of the solution is removed with a pipette and transferred to a 250 mL volumetric flask for the second dilution, and the volumetric flask is filled with internal standard and 10% hydrochloric acid up to the 250 mL mark, and then homogenized. Finally, this 50 mL solution is used for ICP-OES measurement.
[0076] B) Particle size The particle size distribution (PSD) of the cathode active material powders is measured by laser diffraction particle size analysis using a Malvern Mastersizer 3000 equipped with a Hydro MV wet dispersion accessory after dispersing each powder sample in an aqueous medium. Sufficient ultrasonic irradiation and stirring are applied and appropriate surfactants are introduced to improve the dispersion of the powders. D50 is defined as the particle size at 50% of the cumulative volume percent distribution obtained from the Malvern Mastersizer 3000 by Hydro MV measurement.
[0077] C) X-ray photoelectron spectroscopy In the present invention, X-ray photoelectron spectroscopy (XPS) is used to analyze the surface of the positive electrode active material powder particles. In the XPS measurement, the signal is obtained from the top of the sample, i.e., the first few nanometers (e.g., 1 nm to 10 nm) of the surface layer. Therefore, all elements measured by XPS are contained in the surface layer.
[0078] For the surface analysis of the positive electrode active material powder particles, XPS measurements are performed using a Thermo K-α+ spectrometer (Thermo Scientific). Monochromatic Al Kα radiation (hυ=1486.6 eV) is used with a spot size of 400 μm and a measurement angle of 45°. A broad survey scan to identify the elements present on the surface is performed with a pass energy of 200 eV. The C1s peak with maximum intensity (or center) at a binding energy of 284.8 eV is used as the calibration peak position after data collection. Then, for each identified element, at least 10 precise narrow scans at 50 eV are performed to determine the exact surface composition.
[0079] Curve fitting was performed with CasaXPS version 2.3.19PR1.0 (Casa Software) using Shirley-type background processing and Scofield sensitivity coefficients. Fitting parameters are according to Table 1a. The line shape GL(30) is the Gaussian / Lorentzian product formula at the 70% Gaussian and 30% Lorentzian lines.
[0080] [Table 1]
[0081] For Zr and Co peaks, limits are set for each specified peak according to Table 1b.
[0082] [Table 2]
[0083] The surface content of Zr determined by XPS is expressed as the mole fraction of Zr in the surface layer of a particle divided by the total content of Ni, Mn, Co and Zr in that surface layer, which is calculated as follows:
[0084]
number
[0085] D) Sulfide solid-state battery testing D1) Preparation of sulfide solid-state battery Preparation of the positive electrode: For the preparation of the positive electrode, a slurry containing the positive electrode active material powder, Li-PS based solid electrolyte, carbon (Super-P, Timcal), and binder (RC-10, Arkema) in a weight ratio of 64.0:30.0:3.0:3.0 in butyl acetate solvent is mixed in an Ar-filled glove box. The slurry is cast onto one side of an aluminum foil, and the slurry-coated foil is subsequently dried in a vacuum oven to obtain the positive electrode. The resulting positive electrode is punched out to a diameter of 10 nm, with an active material loading of approximately 4 mg / cm. 2 It is.
[0086] Preparation of the negative electrode: For preparation of the negative electrode, a Li foil (diameter 3 mm, thickness 100 μm) is centered on top of an In foil (diameter 10 nm, thickness 100 μm) and pressed to form a Li-In alloy negative electrode.
[0087] Separator For the preparation of the separator, which also functions as a solid electrolyte in the battery, the Li-PS-based solid electrolyte is pelletized under a pressure of 250 MPa to obtain a pellet thickness of 100 μm.
[0088] Assembly of the cell The sulfide solid-state battery is assembled in an argon-filled glove box from bottom to top in the following order: cathode with Al current collector with coated part on top - separator - anode with Li side up - Cu current collector. The stacked components are pressed together at a pressure of 250 MPa and placed in an external cage to prevent air exposure.
[0089] D2) Test method The test method is a conventional "constant cut-off voltage" test. Conventional cell testing in the present invention follows the schedule shown in Table 2. Each cell is cycled at 60°C using a Toscat-3100 computer-controlled galvanostatic cycling station (manufactured by Toyo).
[0090] In this schedule, a 1C current definition of 160mA / g is used. The initial charge capacity (CQ1) and discharge capacity (DQ1) are measured from 4.3V to 2.5V (Li / Li + ) or 3.7V~1.9V(InLi / Li + ) voltage range, at a C-rate of 0.1C, in constant current mode (CC).
[0091] The efficiency EF is expressed as a percentage as follows:
[0092]
number
[0093] [Table 3]
[0094] E) Carbon analyzer The carbon content of the cathode active material powder is measured by a Horiba Emia-Expert carbon / sulfur analyzer. 1 g of the cathode active material powder is placed in a ceramic crucible in a high frequency induction furnace. 1.5 g of tungsten and 0.3 g of tin as promoters are added to the crucible. The powder is heated at a programmable temperature where the gases produced during combustion are analyzed by an infrared detector. CO 2 and CO analysis to determine carbon concentration.
[0095] F) Surface area analysis The specific surface area of the positive electrode active material is measured by the Brunauer-Emmett-Teller (BET) method by using a Micromeritics Tristar II 3020. Prior to the measurement, the powder sample was immersed in nitrogen (N 2 ) gas at 300°C for 1 hour. The dried powder is placed in a sample tube. The sample is then degassed at 30°C for 10 minutes. The nitrogen adsorption test is performed in this device at 77K. The nitrogen adsorption / desorption isotherm curve is obtained to determine the m 2 The total specific surface area of the sample in units of / g is derived.
[0096] The invention is further illustrated by the following (non-limiting) examples.
[0097] Comparative Example 1 A single crystal positive electrode active material, labeled CEX (Comparative) 1, was prepared according to the following steps. Step 1) Preparation of transition metal oxide hydroxide precursor: Metal composition Ni 0.8 Mn 0.1 Co 0.1 Nickel-based transition metal oxide hydroxide powder (TMH1) with the above formula was prepared by co-precipitation process in a large-scale continuous stirred tank reactor (CSTR) containing mixed nickel manganese cobalt sulfate, sodium hydroxide, and ammonia. Step 2) Oxidation of the precursor: TMH1 prepared in step 1) was heated at 400° C. for 7 hours in an oxidizing atmosphere to obtain a heating product. Step 3) First mixing: The transition metal-based oxide hydroxide precursor and LiOH as the lithium source were homogeneously mixed in an industrial blending device with a lithium to metal M′ (Li / M′) ratio of 1.02 to obtain a first mixture. Step 4) First heating: The first mixture from step 3) was heated at 730° C. for 10 hours under oxygen atmosphere. The heated product was crushed, classified and sieved to obtain a first heated product. Step 5) Second heating: The first heating product from step 4) was heated at 920° C. for 10 hours under oxygen atmosphere to obtain a second heating product. Step 6) Wet bead milling: The second heating product from step 5) was bead milled in a solution containing 0.5 mol% Co relative to the total molar content of Ni, Mn, and Co in the second heating product, followed by drying and sieving to obtain a milled product. The weight ratio of solid to solution for bead milling was 1:1 and was performed for 20 minutes. Step 7) Second blending: The milled product from step 6) is mixed in an industrial blender with CO in an amount of 1000 ppm based on the total molar content of Ni, Mn, and Co in the milled product, respectively. 3 O 4 A second mixture was obtained by mixing with 1.5 mol % Co from LiOH and 4 mol % Li from LiOH. Step 8) Third heating: The second mixture from step 7) was heated at 760° C. for 10 hours under an oxidizing atmosphere, followed by grinding and sieving with the addition of 250 ppm alumina powder to obtain an intermediate product. Step 9) Wet mixing: The following steps 9a) to 9c) were applied to introduce Zr into the positive electrode active material. Step 9a) Preparation of Zr solution: 0.8 mol % Zr from Zr propoxide (70 wt % Zr propoxide in n-propanol solution), 1.6 mol % Li from Li ethoxide powder, and ethanol solvent, relative to the total molar content of Ni, Mn, and Co, respectively, in the intermediate product, were mixed to form a solution. The amount of ethanol solvent was 55 wt % of the total weight of the designated intermediate product to be mixed in step 9b). Step 9b) Mixing: The intermediate product obtained from step 8) was mixed with the Zr solution prepared in step 9a) in a heatable reactor for 20 minutes. Step 9c) Heating: Heat of 70° C. was applied to the reactor of step 9b) while simultaneously connecting the reactor to a vacuum pump to evaporate the volatile phase. A dry powder was obtained from this step. Step 10) Fourth Heat: The dried powder from step 9c) is heated at 350° C. for 6 hours under oxygen atmosphere to obtain CEX1 with M′ containing Ni, Mn, Co, and Zr with Ni:Mn:Co:Zr ratio of 0.79:0.10:0.11:0.007 by ICP-OES. CEX1 has a D50 of 4 μm.
[0098] Example 1 A single crystal positive electrode active material, labeled EX (Example) 1, was prepared according to the following steps. Step 1) Preparation of Zr solution: 0.8 mol% Zr from Zr propoxide (70 wt% Zr-propoxide in n-propanol solution) was dissolved in 3 grams of ethanol. Step 2) Slurry preparation: 70 grams of the intermediate product obtained from step 8) in the preparation of CEX1 was mixed with 1.6 mol % LiOH and 4 mol % water, both with respect to M', and 26 grams of ethanol to form a slurry. Step 3) Mixing: The Zr solution prepared from step 1) and the slurry prepared from step 2) were mixed and stirred at room temperature for 15 hours, followed by filtration and drying in vacuum at 80° C. for 6 hours. Step 4) Heating: The dried powder from step 3) was heated at 350° C. for 6 hours under oxygen atmosphere to obtain EX1 with M′ containing Ni, Mn, Co, and Zr with Ni:Mn:Co:Zr ratio of 0.79:0.10:0.11:0.007 by ICP-OES. EX1 has a D50 of 4 μm.
[0099] Comparative Example 2 A single crystalline positive electrode active material, labeled CEX2, was prepared according to the following steps. Step 1) Preparation of transition metal oxide hydroxide precursor: Metal composition Ni 0.85 Mn 0.07 Co 0.08 Nickel-based transition metal oxide hydroxide powder (TMH2) with the above formula was prepared by co-precipitation process in a large-scale continuous stirred tank reactor (CSTR) containing mixed nickel manganese cobalt sulfate, sodium hydroxide, and ammonia. Step 2) Oxidation of the precursor: The TMH2 prepared in step 1) was heated at 400° C. for 7 hours in an oxidizing atmosphere to obtain a heating product. Step 3) First Mixing: The heating product prepared in step 2) was mixed with LiOH in an industrial blender to obtain a first mixture with a lithium to metal M' (Li / M') ratio of 0.96. Step 4) First heating: The first mixture from step 3) was heated at 890° C. for 11 hours under an oxidizing atmosphere to obtain a first heating product. Step 5) Wet bead milling: The first heating product from step 4) was bead milled in a solution containing 0.5 mol% Co relative to the total molar content of Ni, Mn, and Co in the first heating product, followed by drying and sieving to obtain a milled product. The weight ratio of solid to solution for bead milling was 6:4 and was performed for 20 minutes. Step 6) Second blending: The milled product from step 5) is mixed in an industrial blender with CO in an amount of 1000 ppm based on the total molar content of Ni, Mn, and Co in the milled product, respectively. 3 O 4 A second mixture was obtained by mixing with 1.5 mol % Co from LiOH and 7.5 mol % Li from LiOH. Step 7) Second heating: The second mixture from step 6) was heated at 760° C. for 10 hours under an oxidizing atmosphere, followed by grinding and sieving with the addition of 250 ppm alumina powder to obtain an intermediate product. Step 8) Wet mixing: The following steps 8a) to 8c) were applied to introduce Zr into the positive electrode active material. Step 8a) Preparation of Zr solution: 0.75 mol % Zr from Zr propoxide (70 wt % Zr propoxide in n-propanol solution), 1.5 mol % Li from Li ethoxide powder, and ethanol solvent were mixed relative to the total molar content of Ni, Mn, and Co in the intermediate product, respectively, to form a solution. The amount of ethanol solvent was 55 wt % of the total weight of the designated intermediate product to be mixed in step 8b). Step 8b) Mixing: The intermediate product obtained from step 7) was mixed with the Zr solution prepared in step 7a) in a heatable reactor for 20 minutes. Step 8c) Heating: Heat of 70° C. was applied to the reactor of step 8b) while simultaneously connecting the reactor to a vacuum pump to evaporate the volatile phase. A dry powder was obtained from this step. Step 9) Third Heating: The dried powder from step 8c) is heated at 350° C. for 6 hours under oxygen atmosphere to obtain CEX2 with M′ containing Ni, Mn, Co, and Zr with Ni:Mn:Co:Zr ratio of 0.84:0.07:0.09:0.007 by ICP-OES. CEX2 has a D50 of 4 μm.
[0100] Example 2 A single crystalline positive electrode active material, labeled EX2.1, was prepared according to the following steps. Step 1) Preparation of Zr solution: 0.75 mol% Zr from Zr propoxide (70 wt% Zr-propoxide in n-propanol solution) was dissolved in 3 grams of ethanol. Step 2) Slurry preparation: 70 grams of the intermediate product obtained from step 7) in the preparation of CEX2 was mixed with 1.5 mol % LiOH and 3.75 mol % water, both relative to M', and 26 grams of ethanol to form a slurry. Step 3) Mixing: The Zr solution prepared from step 1) and the slurry prepared from step 2) were mixed and stirred at room temperature for 15 hours, followed by filtration and drying in vacuum at 80° C. for 6 hours. Step 4) Heating: The dried powder from step 3) is heated at 350° C. for 6 hours under oxygen atmosphere to obtain EX2.1 having M′ containing Ni, Mn, Co, and Zr with Ni:Mn:Co:Zr ratio of 0.84:0.07:0.09:0.007 by ICP-OES. EX2.1 has a D50 of 4 μm.
[0101] EX2.2 uses 0.6 mol% Zr from Zr propoxide in step 1) and 1.2 mol% Li and 3 mol% H from LiOH in step 2).2 EX2.2 was prepared according to the same method as EX2.1, except that O was used. EX2.2 has M' containing Ni, Mn, Co, and Zr with a Ni:Mn:Co:Zr ratio of 0.84:0.07:0.09:0.006 obtained by ICP-OES. EX2.2 has a D50 of 4 μm.
[0102] EX2.3 uses 0.45 mol% Zr from Zr propoxide in step 1) and 0.9 mol% Li and 2.25 mol% H from LiOH in step 2). 2 EX2.3 was prepared according to the same method as EX2.1, except that O was used. EX2.3 has M' containing Ni, Mn, Co, and Zr with a Ni:Mn:Co:Zr ratio of 0.84:0.07:0.09:0.004 obtained by ICP-OES. EX2.3 has a D50 of 4 μm.
[0103] Comparative Example 3 A single crystal positive electrode active material, labeled CEX3, was prepared according to the following steps. Step 1) Preparation of transition metal oxide hydroxide precursor: Metal composition Ni 0.63 Mn 0.22 Co 0.15 Nickel-based transition metal oxide hydroxide powder (TMH3) with the above formula was prepared by co-precipitation process in a large-scale continuous stirred tank reactor (CSTR) containing mixed nickel manganese cobalt sulfate, sodium hydroxide, and ammonia. Step 2) First mixing: TMH3 prepared in step 1) is mixed with Li 2 CO 3 and were mixed in an industrial blender to obtain a first mixture having a lithium to metal M′ (Li / M′) ratio of 0.85. Step 3) First heating: The first mixture from step 2) was heated at 900° C. for 10 hours under dry air atmosphere to obtain a first heating cake. Step 4) Second Mixing: The first cooked cake from step 3) was mixed with LiOH in an industrial blender to obtain a second mixture with a lithium to metal M' (Li / M') ratio of 1.05. Step 5) Second Heating: The second mixture from step 4) was heated at 950° C. for 10.2 hours under dry air, followed by wet milling, drying, and sieving to obtain the second heating product. Step 6) Third mixing: The second heating product from step 5) is mixed with 2 mol% CO based on the total molar content of Ni, Mn, and Co, respectively. 3 O 4 and 5 mol % LiOH to obtain a third mixture. Step 7) Third Heating: The third mixture from step 6) was heated at 775° C. for 12 hours under dry air to produce an intermediate product. Step 8) Wet mixing: The following steps 8a) to 8c) were applied to introduce Zr into the positive electrode active material. Step 8a) Preparation of Zr solution: 0.46 mol% Zr from Zr propoxide (70 wt% Zr propoxide in n-propanol solution), 0.92 mol% Li from Li ethoxide powder, and ethanol solvent were mixed to form a solution, relative to the total molar content of Ni, Mn, and Co in the intermediate product, respectively. The amount of ethanol solvent was 55 wt% of the total weight of the designated intermediate product to be mixed in step 8b). Step 8b) Mixing: The intermediate product obtained from step 7) was mixed with the Zr solution prepared in step 8a) in a heatable reactor for 20 minutes. Step 8c) Heating: Heat of 70° C. was applied to the reactor of step 8b) while simultaneously connecting the reactor to a vacuum pump to evaporate the volatile phase. A dry powder was obtained from this step. Step 9) Fourth Heat: The dried powder from step 8c) is heated at 350° C. for 6 hours under oxygen atmosphere to obtain CEX3 with M′ containing Ni, Mn, Co, and Zr with Ni:Mn:Co:Zr ratio of 0.62:0.22:0.16:0.004 by ICP-OES. CEX3 has a D50 of 6 μm.
[0104] Example 3 A single crystal positive electrode active material, labeled EX3, was prepared according to the following steps. Step 1) Preparation of Zr solution: 0.46 mol% Zr from Zr propoxide (70 wt% Zr-propoxide in n-propanol solution) was dissolved in 3 grams of ethanol. Step 2) Slurry preparation: 70 grams of the intermediate product obtained from step 7) in the preparation of CEX3 was mixed with 0.92 mol % LiOH and 2.3 mol % water, both relative to M', and 26 grams of ethanol to form a slurry. Step 3) Mixing: The Zr solution prepared from step 1) and the slurry prepared from step 2) were mixed and stirred at room temperature for 15 hours, followed by filtration and drying in vacuum at 80° C. for 6 hours. Step 4) Heating: The dried powder from step 3) was heated at 350° C. for 6 hours under oxygen atmosphere to obtain EX3 having M′ containing Ni, Mn, Co, and Zr with Ni:Mn:Co:Zr ratio of 0.62:0.22:0.16:0.004 by ICP-OES. EX2.1 has a D50 of 6 μm.
[0105] Comparative Example 4 A polycrystalline positive electrode active material, labeled CEX4, was prepared according to the following steps. Step 1) Preparation of transition metal oxide hydroxide precursor: Metal composition Ni 0.83 Mn 0.12 Co 0.05 Nickel-based transition metal oxide hydroxide powder (TMH4) with the above formula was prepared by co-precipitation process in a large-scale continuous stirred tank reactor (CSTR) containing mixed nickel manganese cobalt sulfate, sodium hydroxide, and ammonia. Step 2) First Mixing: TMH4 prepared in step 1) was mixed with LiOH in an industrial blender to obtain a first mixture with a lithium to metal ratio of 0.96. Step 3) First heating: The first mixture from step 2) was heated at 765° C. for 10 hours under an oxidizing atmosphere to obtain a first heating product, which was then crushed and sieved. Step 4) Second mixing: The first heating product from step 3) and LiOH as lithium source were homogeneously mixed in an industrial blending device with a lithium to metal M' (Li / M') ratio of 1.02 to obtain a second mixture. Step 5) Second heating: The second mixture from step 4) was heated at 780° C. for 12 hours under oxygen atmosphere to obtain an intermediate product. Step 6) Wet mixing: The following steps 6a) to 6c) were applied to introduce Zr into the positive electrode active material. Step 6a) Preparation of Zr solution: 0.63 mol % Zr from Zr propoxide (70 wt % Zr propoxide in n-propanol solution), 1.26 mol % Li from Li ethoxide powder, and ethanol solvent were mixed with respect to the total molar content of Ni, Mn, and Co in the intermediate product, respectively, to form a solution. The amount of ethanol solvent was 55 wt % of the total weight of the designated intermediate product to be mixed in step 6b). Step 6b) Mixing: The intermediate product obtained from step 5) was mixed with the Zr solution prepared in step 6a) in a heatable reactor for 20 minutes. Step 6c) Heating: Heat of 70° C. was applied to the reactor of step 6b) while simultaneously connecting the reactor to a vacuum pump to evaporate the volatile phase. A dry powder was obtained from this step. Step 7) Third Heating: The dried powder from step 6c) is heated at 350° C. for 6 hours under oxygen atmosphere to obtain CEX4 with M′ containing Ni, Mn, Co, and Zr with Ni:Mn:Co:Zr ratio of 0.82:0.12:0.05:0.006 by ICP-OES. CEX4 has a D50 of 6 μm.
[0106] Example 4 A polycrystalline positive electrode active material labeled EX4 was prepared according to the following steps. Step 1) Preparation of Zr solution: 0.63 mol% Zr from Zr propoxide (70 wt% Zr-propoxide in n-propanol solution) was dissolved in 3 grams of ethanol. Step 2) Slurry preparation: 70 grams of the intermediate product obtained from step 5) in the preparation of CEX4 was mixed with 1.26 mol % LiOH and 3.15 mol % water, both relative to M', and 26 grams of ethanol to form a slurry. Step 3) Mixing: The Zr solution prepared from step 1) and the slurry prepared from step 2) were mixed and stirred at room temperature for 15 hours, followed by filtration and drying in vacuum at 80° C. for 6 hours. Step 4) Heating: The dried powder from step 3) was heated at 350°C for 6 hours under oxygen atmosphere to obtain EX3 having M' containing Ni, Mn, Co, and Zr with Ni:Mn:Co:Zr ratio of 0.83:0.120:0.050:0.006 by ICP-OES. EX4 has a D50 of 6 μm.
[0107] Comparative Example 5 A polycrystalline positive electrode active material, labeled CEX5, was prepared according to the following steps. Step 1) Preparation of transition metal oxide hydroxide precursor: Metal composition Ni 0.625 Mn 0.175 Co 0.200 Nickel-based transition metal oxide hydroxide powder (TMH5) with the above formula was prepared by co-precipitation process in a large-scale continuous stirred tank reactor (CSTR) containing mixed nickel manganese cobalt sulfate, sodium hydroxide, and ammonia. Step 2) First mixing: The transition metal-based oxide hydroxide precursor and LiOH as the lithium source were homogeneously mixed in an industrial blending device with a lithium to metal M′ (Li / M′) ratio of 1.03 to obtain a first mixture. Step 3) First heating: The first mixture from step 2) was heated at 830° C. for 10 hours under oxygen atmosphere. The heated product was crushed, classified and sieved to obtain an intermediate product. Step 4) Wet mixing: The following steps 4a) to 4c) were applied to introduce Zr into the positive electrode active material. Step 4a) Preparation of Zr solution: 0.25 mol % Zr from Zr propoxide (70 wt % Zr propoxide in n-propanol solution), 0.5 mol % Li from Li ethoxide powder, and ethanol solvent, relative to the total molar content of Ni, Mn, and Co in the intermediate product, respectively, were mixed to form a solution. The amount of ethanol solvent was 55 wt % of the total weight of the designated intermediate product to be mixed in step 4b). Step 4b) Mixing: The intermediate product obtained from step 3) was mixed with the Zr solution prepared in step 4a) in a heatable reactor for 20 minutes. Step 4c) Heating: Heat of 70° C. was applied to the reactor of step 4b) while the reactor was connected to a vacuum pump to evaporate the volatile phase. A dry powder was obtained from this step. 5) Second heating: The dried powder from step 4c) is heated at 350° C. for 6 hours under oxygen atmosphere to obtain CEX5 with M′ containing Ni, Mn, Co, and Zr with Ni:Mn:Co:Zr ratio of 0.62:0.17:0.20:0.002 by ICP-OES. CEX3.2 has a D50 of 10 μm.
[0108] Example 5 A polycrystalline positive electrode active material labeled EX5 was prepared according to the following steps. Step 1) Preparation of Zr solution: 0.25 mol% Zr from Zr propoxide (70 wt% Zr-propoxide in n-propanol solution) was dissolved in 3 grams of ethanol. Step 2) Slurry preparation: 70 grams of the intermediate product obtained from step 3) in the preparation of CEX5 was mixed with 0.5 mol % LiOH and 1.25 mol % water, both relative to M', and 26 grams of ethanol to form a slurry. Step 3) Mixing: The Zr solution prepared from step 1) and the slurry prepared from step 2) were mixed and stirred at room temperature for 15 hours, followed by filtration and drying in vacuum at 80° C. for 6 hours. Step 4) Heating: The dried powder from step 3) was heated at 350° C. for 6 hours under oxygen atmosphere to obtain EX3 having M′ containing Ni, Mn, Co, and Zr with Ni:Mn:Co:Zr ratio of 0.62:0.17:0.20:0.002 by ICP-OES. EX5 has a D50 of 10 μm.
[0109] [Table 4] * For the molar contents of Ni, Mn, Co and Zr
[0110] Table 3 summarizes the composition, surface area, and corresponding electrochemical properties of the examples and comparative examples. x indicates the atomic ratio (molar ratio) of Zr to the total atomic fraction of Ni, Mn, Co, and Zr. Zr greater than 0 x indicates that Zr is present at the surface of the positive electrode active material in conjunction with XPS measurements where the signal is acquired from the very top of the sample, i.e., the first few nanometers (e.g., 1 nm to 10 nm) of the surface layer.
[0111] CEX1 and EX1 are single crystal positive electrode active materials having a Ni content of about 78.4 mol% and a Zr content of about 0.72 mol%. Due to the difference in the process of Zr incorporation, EX1 has a lower carbon content and a higher Zr content compared to CEX1. x Higher Zr x It is further observed that the C ratio is related to improved efficiency of solid-state batteries.
[0112] CEX2 and EX2.1 are single crystal positive electrode active materials having a Ni content of about 83.6 mol% and a Zr content of about 0.67 mol%. EX2.1 prepared according to the method of the present invention has a higher Zr content compared to CEX2. x EX2.2 and EX2.3 contain Zr in amounts of 0.56 mol % and 0.40 mol %, respectively. Both examples / comparative examples have the same Zr content as EX2.1.x and C to achieve improved cell efficiency.
[0113] The present invention is further illustrated by a comparison of CEX3 with EX3, CEX4 with EX4, and CEX5 with EX5. CEX3 and EX3 are single crystal cathode active materials with Ni content of about 61.7 mol% and Zr content of about 0.41 mol%. CEX4 and EX4 are polycrystalline cathode active materials with Ni content of about 82.5 mol% and Zr content of about 0.57 mol%. Finally, CEX5 and EX5 are polycrystalline cathode active materials with Ni content of about 62.4 mol% and Zr content of about 0.25 mol%. All these examples have a higher Zr content than the comparative examples. x The results show improved efficiency related to the ratio of Ni to C. The invention works with both single crystal and polycrystalline materials, with Ni ranging from 55.0 mol % to 95.0 mol %.
Claims
1. A positive electrode active material for a solid-state battery, the positive electrode active material comprising Li, M′, and oxygen, wherein M′ is Ni with a content x, where 55.0 mol%≦x≦95.0 mol%, Mn with a content y of 0.0 mol%≦y≦40.0 mol%; Co with a content z of 0.0 mol%≦z≦40.0 mol%; D with a content a of 0.0 mol%≦a≦2.0 mol%, where D is at least one element other than Li, Ni, Mn, Co, and O; Zr having a content b, where 0.01 mol%≦b≦5.0 mol%, x, y, z, a, and b are measured by ICP-OES; x+y+z+a+b is 100.0 mol%, The positive electrode active material has a Zr content of Zr x Zr x is determined by XPS analysis, Zr x is expressed as a mole fraction compared to the sum of the mole fractions of Co, Mn, Ni, and Zr as determined by XPS analysis; the positive electrode active material comprises carbon in an amount C as measured by a carbon analyzer, C being in weight percent based on the total weight of the positive electrode active material; Zr x The ratio of C to 52-0.413 x to 42-0.413 x (weight%) -1 That is, the positive electrode active material.
2. 2. The positive electrode active material according to claim 1, wherein D is at least one element other than Li, Ni, Mn, Co, Zr, and O.
3. 2. The cathode active material of claim 1, wherein D comprises at least one element from the group consisting of Al, B, Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, Ti, Y, V, W, and Zn, preferably Al, B, Cr, Nb, S, Si, Ti, Y, and W.
4. Zr x and C ratio is 50-0.413.x to 43-0.413.x (weight%) -1 The positive electrode active material according to claim 1 ,
5. 2. The positive electrode active material of claim 1, wherein C≦0.15 wt %, based on the total weight of the positive electrode active material.
6. The surface area SA determined by BET measurements, the ratio of C to SA being at most 0.25% by weight (g / m 2 2. The positive electrode active material according to claim 1 .
7. The positive electrode active material according to claim 1 , wherein 60.0 mol %≦x≦90.0 mol %.
8. The positive electrode active material according to claim 1 , wherein 0.05 mol %≦b≦2.5 mol %.
9. The cathode active material of claim 1 , wherein the cathode active material is a polycrystalline powder.
10. 9. The cathode active material of claim 8, wherein the secondary particle median diameter D50 is at least 2.0 μm and at most 15.0 μm, as determined by laser diffraction particle size analysis.
11. A method for producing a positive electrode active material, comprising the steps of: Preparing a slurry of a lithium transition metal based oxide compound, Li, water, and alcohol; mixing the slurry with a Zr source; and heating the mixture at a temperature of 250° C. to 500° C. in an oxidizing atmosphere in a furnace for a time period of 1 hour to 20 hours to obtain the cathode active material.
12. 12. The method of claim 11, comprising the further step of filtering and drying the mixture prior to heating the mixture.
13. The method of claim 11, wherein the Zr source is Zr-propoxide.
14. 12. The method of claim 11, wherein the amount of water in the slurry is 0.5 mol % to 25.0 mol % relative to the metal content in the lithium transition metal oxide compound.
15. The method according to any one of claims 11 to 14, wherein the positive electrode active material is the positive electrode active material according to any one of claims 1 to 10.
16. A solid-state battery comprising the positive electrode active material according to any one of claims 1 to 10.
17. 17. The solid-state battery of claim 16 comprising a sulfide-based solid electrolyte comprising Li, P, and S.
18. 20. Use of the battery of claim 16 in any one of a portable computer, a tablet, a mobile phone, an energy storage system, an electric vehicle, or a hybrid electric vehicle.
Citation Information
Patent Citations
Positive electrode active material for nonaqueous electrolyte secondary battery, fluid dispersion used in producing the same, and production method thereof
JP2016072071A
Positive electrode active material for lithium secondary battery, positive electrode for lithium secondary battery, and lithium secondary battery
JP2022043852A
Positive electrode active material for lithium ion secondary batteries, method for producing said positive electrode active material, and lithium ion secondary battery
WO2021251416A1